Visual processing of musical syntax and its relationship to sight-reading ability - Yeoeun Lim; Andrew Goldman (PLoS ONE, 2026)
Sight-reading—performing music by reading written notation without prior practice—is a fundamental skill for musicians, yet there is considerable variability in sight-reading ability that technical proficiency alone does not explain. Instead, cognitive mechanisms may explain differences in sight-reading expertise. Prediction of upcoming music is crucial for fluent sight-reading, and these predictions rely on knowledge of harmonic syntax—principles for ordering musical elements. Two research gaps remain: First, no study has directly examined how individual differences in sensitivity to harmonic syntax may relate to sight-reading proficiency. Second, while studies have shown that harmonic syntax can be processed through visual observation of musical actions without sound, it remains unclear whether similar sensitivity emerges during the reading of symbolic musical notation—a context more analogous to sight-reading, and parallel to word reading in language. To address these gaps, 20 skilled pianists completed three tasks: sight-reading, self-paced reading of chord progressions, and an audiation test. Using computational modeling to quantify harmonic predictability, we found that harmonically less predictable chords required significantly longer reading times, providing evidence that visual processing of symbolic music notation exhibits sensitivity to harmonic predictability. However, the degree of this sensitivity showed no significant correlation with sight-reading proficiency or audiation ability, although our sample size may have been too small to detect small interaction effects. Instead, accurate sight-readers showed faster chord reading times regardless of harmonic predictability, suggesting that general visual processing efficiency distinguishes proficient sight-readers. These findings extend prior evidence for visual harmonic processing to the domain of symbolic notation, suggesting that sensitivity to harmonic syntax may operate through written musical symbols without auditory input or motor imitation. Simultaneously, they suggest sight-reading may be a multi-dimensional skill where visual fluency may be more critical than sophisticated syntactic knowledge, suggesting the importance of developing visual processing efficiency for sight-reading expertise.